Design of Robust Steerable Broadband Beamformers with Spiral Arrays and the Farrow Filter Structure - Lai, Chiong; Nordholm, Sven; Leung, Yee-Hong (Ortra, 2010)
This paper extends the design of steerable broadband beamformers by incorporating robustness in the design formulation to cater for microphone mismatches and other non-ideal characteristics. In our method, a 2 norm constraint on the filter weights is imposed in the design optimisation problem. This constraint limits the 2-norm of the filter weights, thus reducing the sensitivity of the beamformer towards the non-ideal characteristics of the microphones. Design examples and comparisons are presented to illustrate our approach.